Response of Pseudomonas putida to Complex, Aromatic‐Rich Fractions from Biomass. Issue 17 (30th April 2020) - Park, Mee‐Rye; Chen, Yan; Thompson, Mitchell; Benites, Veronica T.; Fong, Bonnie; Petzold, Christopher J.; Baidoo, Edward E. K.; Gladden, John M.; Adams, Paul D.; Keasling, Jay D.; Simmons, Blake A.; Singer, Steven W.
Abstract: There is strong interest in the valorization of lignin to produce valuable products; however, its structural complexity has been a conversion bottleneck. Chemical pretreatment liberates lignin‐derived soluble fractions that may be upgraded by bioconversion. Cholinium ionic liquid pretreatment of sorghum produced soluble, aromatic‐rich fractions that were converted by Pseudomonas putida ( P. putida ), a promising host for aromatic bioconversion. Growth studies and mutational analysis demonstrated that P. putida growth on these fractions was dependent on aromatic monomers but unknown factors also contributed. Proteomic and metabolomic analyses indicated that these unknown factors were amino acids and residual ionic liquid; the oligomeric aromatic fraction derived from lignin was not converted. A cholinium catabolic pathway was identified, and the deletion of the pathway stopped the ability of P. putida to grow on cholinium ionic liquid. This work demonstrates that aromatic‐rich fractions obtained through pretreatment contain multiple substrates; conversion strategies should account for this complexity. Abstract : Walk on the wild type : Cholinium ionic liquid pretreatment of sorghum produces soluble, aromatic‐rich fractions that are converted by Pseudomonas putida, a promising host for aromatic bioconversion. Growth studies and mutational analysis demonstrate that P. putida growth on these fractions depends on the aromatic monomers but unknown factors also contributed.